Coleta seletiva no bairro Atalaia em Aracaju-Sergipe: discurso do sujeito coletivo dos (as) catadores (as) informais de resíduos sólidos recicláveis - Silva, Alam Fabiano Nascimento da (2023)
This research carried out an analysis of the Discourse of the Collective Subject of the population of informal collectors who operate in the Atalaia neighborhood, in the city of Aracaju/SE, about the Selective Collection of Recyclable Solid Waste (RSW). The research sought to identify the type of discourse present in the dialogues and statements that express the way of thinking of a community that shares a certain “world of life”. To achieve this, we opted for the strategic use of the qualitative methodology of analyzing the Collective Subject Discourse. This information is present in the podcast about Selective Collection of Recyclable Waste and describes the dialectic expression of the collectors, through life stories and the relationship with the precarious work of collection in the neighborhood. Specifically, the research objectives were: investigate the socioeconomic reality of the collectors in the face of the informal activity of collection in the Atalaia neighborhood; to understand how the collectors think about the Selective Collection of RSW in the Atalaia neighborhood; reflect in a shared way on the perception of the relationship that the activity of the collectors of the Atalaia neighborhood has with the care of the environment. To advance the paradigm of solid waste management, the research brings with it the possibility of collective construction of liberating communicative actions that represent in a shared way a certain world of life, the one that is present in their social way of thinking. Based on the commercialization potential of recyclable materials from the household disposal of RSW found in the Atalaia neighborhood, and the reality of the collectors in the face of the informal activity of collection. The research also presented a survey of the socioeconomic profile of the sample of 12 collectors, when approaching information about the characterization, identification of the collected materials and the organizational system from collection to final commercialization of these. It was proven that the collectors are able to see the relationship between the activity of collection and the practice of Selective Collection. With little access to formal education, waste collectors have no understanding or contact with any form of Environmental Education. They do not perceive the ethical relationship between the collection activity and the issue of environmental sustainability. It is concluded that the informal collectors of RSW active in the Atalaia neighborhood live in locations close to the neighborhood, in precarious conditions, with little access to formal education, are unemployed, surviving with the informal work of scavenging and some on the help of social programs from the government, work in precarious conditions without the use of Personal Protective Equipment (PPE), survive without guarantees of improvement. With this, the “Recicla Atalaia” brand and the podcast resulting from this research had the possibility of giving visibility to the practice of Selective Collection of RSW in the Atalaia neighborhood, raising awareness of the population and helping the collectors to better manage this waste and better conditions in the work of collection.